Allometric modeling of the bench press and squat: Who is the strongest regardless of body mass? - Dooman, C. S.; Vanderburgh, P. M. (The Journal of Strength and Conditioning Research, 2000)
Olympic weightlifting and powerlifting are 2 competitive contests of strength that use individual weight categories. Because of the positive correlation between body mass and strength, determining the strongest body mass-adjusted competitor involves using a model that appropriately adjusts for a body mass variable. Allometric modeling (AM), using the index y · xb, where y is lifting performance, x is body mass, and b is an allometrically derived exponent, has been proposed as an effective method to correct for body mass. However, recent findings have indicated that a second-order polynomial model may be more appropriate than AM when correcting for body mass in Olympic-style weightlifting (clean and jerk, snatch), which is more a measure of power than of powerlifting. Our purpose was to determine whether AM provides an appropriate fit to men`s powerlifting (bench press, squat, deadlift) world records, which are more a measure of pure strength. All powerlifting world records as of November 1997 were obtained from the International Powerlifting ederation, and body mass was assumed to be the maximal allowable weight for each competitor. Results indicate that AM of world records for the bench press and squat are void of any body mass bias and contain normally distributed residuals. However, the same cannot be said for the deadlift. Therefore, the AM approach appears to be a satisfactory method of determining the strongest body mass-adjusted men in the bench press and squat. We recommend continued use of AM to compare athletes of different body mass using BP · BM0.57 and SQ · BM0.60, where BP is bench press, SQ is squat, and BM is body mass.